Learning and Action Alliance framework to facilitate stakeholder collaboration and social learning in urban flood risk management - O’Donnell, Emily C.; Lamond, Jessica E.; Thorne, C.R. (Elsevier, 2018)
Flood and water management governance may be enhanced through partnership working, intra- and cross-organisational collaborations, and wide stakeholder participation. Nonetheless, barriers associated with ineffective communication, fragmented responsibilities and ‘siloed thinking’ restrict open dialogue and discussion. The Learning and Action Alliance (LAA) framework may help overcome these barriers by enabling effective engagement through social learning, and facilitating targeted actions needed to deliver innovative solutions to environmental problems. By increasing the adaptive capacity of decision-makers and participants, social learning through LAAs may lead to concerted action and sustained processes of behavioural change. In this paper, we evaluate the LAA framework as a catalyst for change that supports collaborative working and facilitates transition to more sustainable flood risk management. We use a case study in Newcastle-upon-Tyne, UK, to demonstrate how the LAA framework brought together disparate City stakeholders to co-produce new knowledge, negotiate innovative actions and, ultimately, work towards implementing a new vision for sustainable urban flood risk management. The shared vision of Newcastle as a ‘Blue-Green City’ that emerged is founded on a strong platform for social learning which increased organisations’ and individuals’ capacities to manage differences in perspectives and behaviours, reframe knowledge, and make collective decisions based on negotiation and conflict resolution. Broad recommendations based on lessons learned from the Newcastle LAA are presented to aid other cities and regions in establishing and running social learning platforms.